CCK and GLP-1 release in response to proteinogenic amino acids using a small intestine ex vivo model in pigs. (22nd March 2022) - Müller, Maximiliano; Van Liefferinge, Elout; Navarro, Marta; Garcia-Puig, Elisabet; Tilbrook, Alan; van Barneveld, Robert; Roura, Eugeni
Abstract: The impact of individual amino acids (AA ) on gut hormone secretion and appetite regulation in pigs remains largely unknown. The aim of the present study was to determine the effect of the 20 proteinogenic AA on the release of the anorexigenic hormones cholecystokinin (CCK ) and glucagon-like peptide 1 (GLP-1 ) in postweaning pigs. Six 25-d-old male piglets (Domestic Landrace × Large White; body weight = 6.94 ± 0.29 kg) were humanely killed for the collection of intestinal segments from the duodenum, jejunum, and ileum. Tissue samples from the three intestinal segments were used to determine which of the regions were more relevant for the analysis of gut peptides. Only the segments with the highest CCK and GLP-1 secretion and expression levels were evaluated with the 20 individual AA. Tissue segments were cut open, cleaned, and stripped of their muscle layer before identical circular samples were collected and incubated in 24-well plates for 1 h (37 °C, 5% v/v CO2 ). The culture broth consisted of a glucose-free KRB buffer containing no added AA (control) or with the addition of 10 mM of 1 of the 20 proteinogenic AA. Following incubation, tissues and supernatant were collected for gene expression and secretion analysis of CCK and GLP-1 levels. CCK secretion and mRNA expression were higher ( P < 0.05) in duodenum when compared with proximal jejunum or ileum, whereas GLP-1/proglucagon levels were higher in ileum vs. duodenum ( P < 0.05) and jejunum ( P < 0.05, for GLP-1 only) in postweaning pigs. Based on these results, the effect of AA on CCK and GLP-1 secretion was studied in the duodenum and ileum, respectively. None of the AA tested stimulated both anorexigenic hormones. Of all the essential AA, Ile, Leu, Met, and Trp significantly ( P < 0.05) stimulated GLP-1 from the ileum, while only Phe stimulated CCK from the duodenum. Of the nonessential AA, amide AA (Gln and Asn) caused the release of CCK, while Glu and Arg increased the release of GLP-1 from the ileum. Interpreting the results in the context of the digestion and absorption dynamics, non-bound AA are quickly absorbed and have their effect on gut peptide secretion limited to the proximal small intestine (i.e., duodenum), thus, mainly CCK. In contrast, protein-bound AA would only stimulate CCK release from the duodenum through feedback mechanisms (such as through GLP-1 secreted mainly in the ileum). Lay Summary: Understanding which dietary amino acids (AA ) may impact the release of gut hormones involved in the modulation of feed intake, such as cholecystokinin (CCK ) and glucagon-like peptide 1 (GLP-1 ), can help improve pig feed formulations. The series of studies presented assessed the effect of the 20 proteinogenic non-bound AA on the secretion of CCK and/or GLP-1 by duodenum, jejunum, and/or ileum samples from postweaning piglets. None of the AA tested stimulated the secretion of both CCK and GLP-1. Among the essential AA (EAA ), Ile, Leu, Met, and Trp significantly stimulated GLP-1 from the ileum, while Phe stimulated CCK from the duodenum. Of the non-essential AA (NEAA ), AA amides Gln and Asn caused the release of CCK, while Glu and Arg increased the release of GLP-1 from the ileum. The results suggest that both non-bound EAA and NEAA participate in appetite control via the release of gut peptides in pigs. Given that CCK was mainly released from duodenum samples (in the pre-enzymatic section of the small intestine), protein-bound AA could only influence CCK release through feedback mechanisms such as through the presence of GLP-1 receptors. Abstract : The individual impact of the 20 proteinogenic amino acids (AA ) on the secretion of the anorexigenic gut hormones cholecystokinin and glucagon-like peptide 1 is described in postweaning pigs using a small intestine ex vivo model. Both non-bound essential and nonessential AA stimulated gut hormone release, demonstrating they play a key role in appetite control in pigs.